6 2x 3 )- 8 =- 2
![6 2x 3 )- 8 =- 2](https://content.bartleby.com/qna-images/question/083e3b78-03ce-452a-9bdc-bd4c54590ded/d3daa95f-631d-420e-bb83-6f3e41895414/q3c2y6v_thumbnail.jpeg)
- 2x 3 )( 3x 6 )( 2 8 0 4x )= 0
- X 2 2x 6 3 8
- 6 2x 5 3 2x 3 8
- 2x 3 8 =( 2x 3 6
- 4 6 2x )( x 3 )=- 8 x 3 2
- 6 2x 4 3 3x * 2 x 8
- 3x 6 2x 8 2x 3
- Solve 6 2x 3 )- 8 =- 2
- 4x 6 2x 3 5x 8 20
- 5 6 2x 3 8 5 24
- 6 2x 3 )= 2 5x 8
- 7 3x 1 )- 6 2x 3 )= 8 x 2 )+ 1
- 3x 4 6 2x 3 8 2x 7 24
- Solve $6 left 2x 3 right )- 8 =- 2
- 6 x 2 4x 3 2x 8